Gas Chromatography Electron Ionization Mass Spectral Analysis of Thio Analogues of Pyrimidine Bases: 5-Bromo-2, 4-di-o-(m- and p-) chloro- (bromo-)benzylthiouracils and 6-methyluracils. (17th January 2012) - Bartkowiak Bartkowiak, G. G.; Wyrzykiewicz Wyrzykiewicz, E. E.; Schroeder Schroeder, G. G.
Abstract : Electron ionization (EI) mass spectral fragmentation routes of twelve 5-bromo-2, 4-di- o -( m - and p -) chloro- (bromo-)benzyl-thiouracils and 6-methyluracils are investigated. The compounds studied are analyzed using gas chromatography/mass spectrometry (GC/MS). Fragmentation pathways, whose elucidation is assisted by accurate mass measurements and metastable transitions, are discussed. Correlation between the abundances of the selected fragment ions of the compounds investigated is discussed. The data obtained make grounds for distinction of structural isomers.